World Immunization Week - Faculty of, Pharmacy (Libyan International Medical University Faculty of Pharmacy, 2018)
World Immunization Week
Faculty of Pharmacy Celebrates World Immunization Week 24-30 April 2018 LIMU First year PharmD students celebrated the World Immunization Week and gave a presentation about vaccines, their importance, types and timings, as well as an explanation of the pharmacist's role in vaccination. First Year PharmD students took this opportunity to increase the awareness of the community about vaccination and to explain to everyone how vaccine keep the world safe.
Keywords: pharm-D; Faculty of Pharmacy; LIMU